Improving the competitiveness of children’s clothes for roller skating by applying ergonomic design method - Omelchenko, G.; Kolosnichenko, M.; Donchenko, S. (Theory and practice of design, 2017)
This article justifies the ways of improving the children’s clothes for roller skating design process through the introduction of modern design technologies. It has been done to improve the competitiveness of future products. The using such ergonomic design tools as "design research" and "design concept", and their harmonious introduction in a typical process of designing, in order to improve it, is important for getting clothes with advanced functionality. This design approach allowed the authors to design a constructive-technological solution of children’s clothes for roller skating with transformation elements. It made the following functions possible: protective function and betweensized adaptive function.